2000
DOI: 10.1016/s0166-0462(00)00039-9
|View full text |Cite
|
Sign up to set email alerts
|

Delivered nonlinear pricing by duopolists

Abstract: This paper presents a model of delivered nonlinear pricing by duopolists operating in a linear city with two types of consumers and having incomplete information. At each location, the higher cost firm offers a uniform price equal to its delivered marginal cost while the lower cost firm offers a nonlinear tariff. For nearby locations, the lower cost firm may charge monopoly nonlinear prices, but as the distance increases the quantity consumed by the low valuation consumer becomes less inefficient than under mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Anderson & Thisse (1989) provide an overview of the literature which developed during the 1980s, as do Eiselt & Laporte (1989), with the latter also exploring the questions which remain unanswered in the literature at the time. Kilkenny & Thisse (1999) and Pires & Sarkar (2000) provide two later literature reviews.…”
Section: Spatial Competitionmentioning
confidence: 99%
“…Anderson & Thisse (1989) provide an overview of the literature which developed during the 1980s, as do Eiselt & Laporte (1989), with the latter also exploring the questions which remain unanswered in the literature at the time. Kilkenny & Thisse (1999) and Pires & Sarkar (2000) provide two later literature reviews.…”
Section: Spatial Competitionmentioning
confidence: 99%
“…These cases are interesting but require additional complex computations. 14 Notice that θ can be reinterpret as the inverse of the marginal utility of income, in a setup where consumers have identical ordinal preferences but differ in their incomes. Wealthier consumers have lower marginal utility of income and consequently higher θ.…”
Section: Mill Nonlinear Pricingmentioning
confidence: 99%
“…Stole studied delivered nonlinear price contracts considering a continuous of consumer types. Delivered nonlinear pricing with a discrete number consumer types was studied by Pires and Sarkar (2000) and Valletti (2002) (they both analyze the locational equilibrium, the former considering price/quantity nonlinear contracts and the latter price/quality nonlinear contracts). The discrete case analysis showed that when firms use delivered nonlinear pricing, in equilibrium, there can be different market regions: monopoly, intermediate and competitive regions.…”
Section: Introductionmentioning
confidence: 99%
“…Stole studies delivered nonlinear price contracts considering a continuous of consumer types. Delivered nonlinear pricing with a discrete number of consumer types was studied by Pires and Sarkar (2000) and Valletti (2002). Both analyze the locational equilibrium, the former considering price/ quantity nonlinear contracts and the latter price/quality nonlinear contracts.…”
Section: Introductionmentioning
confidence: 99%